Development of solar air collectors for drying applications - Karim, M A; Hawlader, Mohammad Nurul Alam (Pergamon, 2004)
In the present work, an experimental study of three types of solar air collectors, namely flat plate, finned and v-corrugated, has been performed towards achieving an efficient design of air collector suitable for a solar dryer. A series of experiments were conducted, based on the ASHRAE standard, under Singapore climatic conditions. The performance of all three collectors is examined over a wide range of operating and design conditions. The v-corrugated collector is found to be the most efficient collector and the flat plate collector the least efficient. The collectors are also studied in double pass mode to investigate the extent of improvement in efficiency that can be achieved without increasing the collector size or cost. Double pass operation of the collector leads to further improvement of the efficiency compared to the single pass of operation. The improvement in efficiency for the double pass mode is most significant in the flat plate collector and least in the v-groove collector. 2003 Elsevier Ltd. All rights reserved.